A New Specimen of Autroraptor cabazai Novas, Pol. Canale, Porfiri and Calvo, 2008 (Dinosauria, Theropoda, Unenlagiidae) from the Latest Cretaceous (Maastrichtian) of Río Negro, Argentina - Currie, Philip J. (2012)
There were considerable differences in Late Cretaceous faunas of the Northern and Southern Hemispheres, although the differences were breaking down during Campanian and Maastrichtian times with the appearance of hadrosaurids in Antarctica and South America, and titanosaurids in North America. However, theropods continued to be separated into northern and southern faunas until paravians were discovered in the Southern Hemisphere (Novas and Puerta, 1997; Forster et al. 1998; Calvo et al. 2004; Makovicky et al. 2005; Novas and Pol, 2005; Novas et al. 2008). During the 2008 field season, a joint expedition to the Bajo de Santa Rosa (Río Negro, Argentina) recovered a second, slightly smaller specimen of Austroraptor cabazai Novas, Pol, Canale, Porfiri and Calvo, 2008 (Novas et al. 2008; Paulina Carabajal et al., 2009). The specimen was identified on the basis of the morphology of the humerus, metatarsal III and pedal phalanx IV-2 (originally identified as IV-1 in the holotype, MML 195). Although the skeleton is incomplete, it preserves bones (radius, ulna, and elements of the metacarpus, metatarsus and pes) that were not recovered with the holotype of this large dromaeosaurid. The description of this second specimen is intended to complement the description of the holotype (Novas et al., 2008), adding information about the limb morphology, particularly the forelimb and foot of this dinosaur.